2017
DOI: 10.1111/echo.13436
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of an automated transthoracic echocardiographic tool for 3D assessment of left heart chamber volumes

Abstract: The current improved version of the automated adaptive algorithm is accurate for the assessment of left heart chamber volumes, albeit a small underestimation of left ventricular end-diastolic volume is seen, when compared with manual 3D echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“…These The gold standard method used in this study was the results provided by the conventional 3D echocardiographic analysis. 10,11 As this method does not implement a specific tool for LA volume analysis, the agreement between 3D and HM results was not assessed. 12 Nevertheless, taking into account the good results obtained for LV enddiastolic, LV end-systolic, and LVEF, it is not difficult to assume that the accuracy for LA volume would be similar.…”
Section: Discussionmentioning
confidence: 99%
“…These The gold standard method used in this study was the results provided by the conventional 3D echocardiographic analysis. 10,11 As this method does not implement a specific tool for LA volume analysis, the agreement between 3D and HM results was not assessed. 12 Nevertheless, taking into account the good results obtained for LV enddiastolic, LV end-systolic, and LVEF, it is not difficult to assume that the accuracy for LA volume would be similar.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several recent publications indicated that HeartModel had strong correlations with the expert manual 3DE and CMR ( r  = 0.84–0.97), high reproducibility and shorter analysis time in adult patient group (14, 15). Using the initial version of HeartModel, Tsang and coworkers reported that LVEF was underestimated and automated LVEDV, LVESV and LAV at LVES were overestimated in HeartModel when compared with manual 3DE measurements (14).…”
Section: Discussionmentioning
confidence: 99%
“…Using the initial version of HeartModel, Tsang and coworkers reported that LVEF was underestimated and automated LVEDV, LVESV and LAV at LVES were overestimated in HeartModel when compared with manual 3DE measurements (14). Still, using the improved version of HeartModel with a default setting of 50% for the global LV boundary for automatic contouring, Spitzer and coworkers demonstrated that only LVEDV were underestimated by HeartModel compared to manual 3DE measurements, with no significant differences in LVESV, LVEF and LAV at LVES (15). Nevertheless, these studies were executed in adults with age ranging from 35 to 86 years, and there were no available data for the application of HeartModel in the adolescent population with or without congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9 This is likely due to the selection of images (only images with good image quality were acceptable), and the extensive use of manually corrected endocardial traces. Some studies have reported that HM presents artificially low volumes.…”
Section: Discrepancies In the Previous Hm Literaturementioning
confidence: 99%